ابن رشد کےکلامی وسیاسی افکاراور مغربی فکر وتہذیب: ایک تحقیقی مطالعہ - Dr Ahmad; Kamran Ali (البصيرة)
Averroes (1126 - 1198) is one of the greatest scholars in the history of Muslim thought. Lots of research has been carried out about his thoughts on theology and politics. It is said that he can bridge the dialogue between Muslim and the western civilization. His study and influence on Western political thought has been examined in this article. Averroes was in favor of religion’s role in politics. He was very fond of Rashidon Caliphate. He has given a list of required attributes of a ruler for good governance. He seems to be interested in democratic values. He talked about rights, social justice and equality in society. He was of the opinion that politics and faith have links. He did not favor sectarianism. He argued his comment through the interpretations of the Divine attributes, God Almighty’s knowledge, the hereafter life, in his theological thoughts. This article comes up with a comparison between Him and western theological and political thoughts. The Western theology is weak and hence it faced the challenge of atheism, while the Muslim scholarship especially Averroes has guided the West in the dark age and helped it in making new thoughts. This research suggests the theological and political thoughts of averroes vital for the today’s Muslim society.